Comparison of enzyme-linked immunosorbent assay (ELISA) technique and complement-fixation test for estimation of cytomegalovirus IgG antibody. Issue 2 (February 1979) - Booth, J C; Hannington, G; Aziz, T A; Stern, H
Abstract : The ELISA technique has been found to be reliable for the detection and titration of cytomegalovirus-specific IgG antibody in serum. It is about six times more sensitive than the CF test although some discrepancies were found between the antibody titres determined by the two methods.